Community Empowerment Under Powerful Government: A Sustainable Tourism Development Path for Cultural Heritage Sites - Hu, Beiming; He, Furong; Hu, Lingshan (Frontiers in Psychology, 2022)
Community participation is the core of sustainable tourism development, however, it encounters obstacles at government-controlled heritage sites in China. This paper examines the status quo of community participation and residents’ empowerment perception through 25 in-depth interviews and 186 questionnaires in the Miao ethnic heritage site of Xijiang Village in southwest China,the findings reveal that: (a)The phenomenon of disempowerment focuses on the political and economic aspects, rather than the social and psychological aspects;(b)Spatial difference affects empowerment perception;(c) Residents desire more political and education empowerment. On this basis, the present research puts forward a comprehensive empowerment system consists of system, information, and education empowerment Which contributes to the theorization of community empowerment between Chinese and Western scholars and provides an alternative path to sustainable tourism development for developing countries’ cultural heritage sites.